Hermeneutika Hukum Lokal dalam Tradisi Pesantren Jawa: Penafsiran Hukum al-Qur’an Kiai Abu Fadhol Senori - Anam Nasrulloh Hasan (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
This study examines the legal hermeneutics developed by Abu Fadhol Senori in his Tafsīr Āyāt al-Aḥkām, a Qur’anic legal commentary produced within the Javanese pesantren tradition. While existing studies of Qur’anic legal exegesis have largely focused on canonical Arabic works or modern reformist approaches, local forms of legal hermeneutics articulated in pesantren contexts remain insufficiently explored. Using a qualitative analytical approach that integrates Qur’anic legal hermeneutics, pesantren epistemology, and the concept of legal locality, this study demonstrates that Senori’s exegetical method operates through a multilayered structure. His interpretation begins with lexical analysis, proceeds to a concise articulation of the verse’s ẓāhir meaning, incorporates authoritative Syafi‘i jurisprudence, and culminates in applied reasoning grounded in Javanese socio-cultural practices. This structure reveals a mode of legal reasoning that preserves fidelity to classical Islamic tradition while remaining responsive to the socio-economic realities of rural Java. The findings show that the pesantren functions not merely as a site of knowledge transmission but as an epistemic regime shaping interpretive strategies through pedagogical condensation, selective citation, and Pegon literacy. The novelty of this study lies in conceptualizing Senori’s tafsīr as a coherent form of local legal hermeneutics, in which cultural elements such as agrarian practices, kinship relations, and communal ethics operate as internal hermeneutical components rather than external illustrations. This study contributes to global Qur’anic studies by highlighting how Islamic legal interpretation is shaped by diverse epistemologies and social ecologies across Muslim societies.